A Review of Molten Metal Flow by Synchronizing of Computational Fluid Dynamics and Validation Through Algorithm Techniques - Saha, Avash Kumar; Majumdar, Sujit (Proceeding International Conference on Religion, Science and Education, 2022)
Computational Fluid Dynamics (CFD) is treading numerical simulation algorithm which is occupying an enormous variety of transitions and different critical modeled which helps in inbounded validation. In this study a justified review of molten metal flow, investigating by CFD analysis, continuity of flow of equation, self-magnetic breakage forces experiment and several validation experiment are been endorsed.Many research paper are been reviewed but with the help of CFD analysis and validation with different algorithm equations but fluidity of molten flow was missing. However, the outcome of the study is to develop an algorithm to measure the effectiveness of forces in molten metal flow.